2017
DOI: 10.1167/iovs.17-22308
|View full text |Cite|
|
Sign up to set email alerts
|

Homocysteine Facilitates Prominent Polygonal Angiogenetic Networks of a Choroidal Capillary Sprouting Model

Abstract: Citation: Lee Y-J, Chiu C-C, Ke C-Y, Tien N, Lin P-K. Homocysteine facilitates prominent polygonal angiogenetic networks of a choroidal capillary sprouting model. Invest Ophthalmol Vis Sci. 2017;58:4332-4343. DOI: 10.1167/iovs.17-22308 PURPOSE. To investigate the effects of homocysteine on choroidal angiogenesis, we established an ex vivo choroidal sprouting explant model and examined the potential growth factors for angiogenesis.METHODS. Choroid fragments with retinal pigment epithelium were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…We previously reported that plasma hcy levels were significantly higher in patients with PCV than in those without PCV 29 , and we found that choroidal angiogenesis was facilitated by hcy in a choroidal capillary sprouting model 30 . Therefore, we assumed that hyperhomocysteinemia may play a role in type I CNV development, including PCV, possibly via an atherosclerosis pathway.…”
Section: Introductionmentioning
confidence: 61%
“…We previously reported that plasma hcy levels were significantly higher in patients with PCV than in those without PCV 29 , and we found that choroidal angiogenesis was facilitated by hcy in a choroidal capillary sprouting model 30 . Therefore, we assumed that hyperhomocysteinemia may play a role in type I CNV development, including PCV, possibly via an atherosclerosis pathway.…”
Section: Introductionmentioning
confidence: 61%
“…Consequently, both significantly increased and/or decreased levels of Cat are strongly indicative for imbalanced production of ROS [39]. -Although its role in BC pathology is inconsistent in the literature, homocysteine (Hcy) has been reported as a proliferation [40] and angiogenesis stimulating metabolite [41]. Moreover, Hcy induces metalloproteinase-2 in a dose-dependent manner [42], which is a prognostic biomarker for tumour aggressiveness and poor outcome in BC patients [43].…”
Section: Biological Interpretation Of the Biomarkers Selectedmentioning
confidence: 99%